Biochemical and Microbiological Quality of Labeo gonius stored in Ice - H., Lilabati; W., Vishwanath (Fishery Technology, 2025)
Biochemical and microbiological qualities of ice-stored Labeo gonius sold in the Imphal market of Manipur were studied over a period of three months from September to November 1994. The fish were nutritionally rich having a protein content of 18.61%. Total volatile base nitrogen values (12.0 mg%) and thiobarbituric acid values were within permissible limit. Total plate counts were the highest in the gill (log 8.00-9.00 cfu g"1) and lowest in the muscle (log 5.00-6.00 cfu g-1). Coliforms, Staphylococcus aureus and faecal streptococci were detected in the samples whereas E. coli and Salmonella were absent.